Impacts of the Coronavirus Pandemic on Families: A Family Systems Perspective - Hensley, Shanna; Harris, Victor William (Advances in Social Sciences Research Journal, 2022)
In the midst of the Coronavirus pandemic, governments around the world implemented lockdowns and stay-at-home orders, requiring many families to quickly adjust to drastic changes in their daily lives. Business closures have caused many individuals to transition to working remotely, deal with the loss of employment, or, for essential employees, face the health risks of continuing to work with the public throughout the pandemic. School and daycare closures have created challenges related to home-schooling and childcare for children who would otherwise be outside of the home each day. From a family systems perspective, it is clear that the disruptions to daily lives and stressors brought on by the pandemic influence the way in which families function. The purpose of this article is to use the family systems theoretical lens to examine impacts of the Coronavirus pandemic on families and the various ways in which families responded. Research on the effects of the events that have taken place throughout the pandemic have provided strong evidence of increased strain within many households, shifts in housework and caregiving responsibilities, and changes to family relationships. Potential implications and what those implications will mean for society are discussed.